1989
DOI: 10.3354/meps052129
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton pigments tn macrozooplankton feces: variability in carotenoid alterations

Abstract: Phytoplankton pigments and their alteration products in macrozooplankton feces were characterized by high-performance liquid chromatography. Fecal material was obtained from animals collected in the Southern California Bight, USA. Different patterns of fecal pigment composition were observed for 2 size classes of macrozooplankton grazers. Fecal material produced by copepoddominated assemblages contained intact phytoplankton carotenoids. Feces produced by 3 relatively large grazers (2 salp species and a pelagc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
3

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 43 publications
(79 reference statements)
3
20
3
Order By: Relevance
“…In addition, the copepods also metab-olized the carotenoids present in the algae, so that ingested fucoxanthin was completely absent from faecal pellets, and diadinoxanthin concentrations were very low. These latter findings contradict the results of previous studies which suggested that carotenoids might be more resistant to digestion than chlorophylls during passage through copepod guts (Kleppel et al 1988, 1991, Nelson 1989.…”
Section: Introductioncontrasting
confidence: 57%
“…In addition, the copepods also metab-olized the carotenoids present in the algae, so that ingested fucoxanthin was completely absent from faecal pellets, and diadinoxanthin concentrations were very low. These latter findings contradict the results of previous studies which suggested that carotenoids might be more resistant to digestion than chlorophylls during passage through copepod guts (Kleppel et al 1988, 1991, Nelson 1989.…”
Section: Introductioncontrasting
confidence: 57%
“…Undegraded carotenoids are found in copepod guts (Keppel 1988) and faecal pellets (Nelson 1989, Roy et al 1989). The same is true for accessory chlorophylls (Vernet & Lorenzen 1987).…”
Section: Phaeocystis Pouchetii Blooms and Vertical Flux Of Organic Mamentioning
confidence: 99%
“…The pigment degradation during digestive processes has been largely investigated in the grazing experiments of copepods (Kleppel & Pieper 1984, Nelson 1989, Swalding & Marcus 1994, BuffanDubau et al 1996. In contrast, few data are available on the pigment destruction in the gut of bivalves (Numagushi 1985, Hawkins et al 1986, Bayne et al 1987, Pastoureaud et al 1996.…”
Section: Stationmentioning
confidence: 99%